Multifunctional hyaluronic acid modified graphene oxide loaded with mitoxantrone for overcoming drug resistance in cancer. (23rd November 2015) - Hou, Lin; Feng, Qianhua; Wang, Yating; Yang, Xiaomin; Ren, Junxiao; Shi, Yuyang; Shan, Xiaoning; Yuan, Yujie; Wang, Yongchao; Zhang, Zhenzhong
Abstract: Multifunctional nanosheets (HA-GO/Pluronic) with targeted chemo-photothermal properties were successfully developed for controlled delivery of mitoxantrone (MIT) to overcome multidrug resistance (MDR). In vitro release profiles displayed that both an acidic environment and a NIR laser could trigger and accelerate the release of a drug, which ensured nanosheets were stable in blood circulation and released MIT within tumor cells under laser irradiation. HA-GO/Pluronic nanosheets were taken up into MCF-7/ADR cells via receptor-mediated endocytosis, which further facilitated escapement of P-gp efflux. Compared with MIT solution, MIT/HA-GO/Pluronic showed greater cytotoxicity and increase in cellular MIT accumulation in MCF-7/ADR cells. Cell apoptosis and cell cycle arrest studies also revealed that MIT/HA-GO/Pluronic was more potent than MIT/GO/Pluronic and MIT solution. The anticancer efficacy in vivo was evaluated in MCF-7 and MCF-7/ADR-bearing mice, and inhibition of tumors by MIT/HA-GO/Pluronic with NIR laser irradiation was the most effective among all MIT formulations. In summary, the MIT/HA-GO/Pluronic system had striking functions such as P-gp reversible inhibitor and anticancer efficacy, and could present a promising platform for drug-resistant cancer treatment.